2020
DOI: 10.1155/2020/9823753
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Optimal Control with Fish Consumption to Prevent the Risk of Coronary Heart Disease

Abstract: According to the World Health Organization (WHO), Chronic Heart Disease (CHD) is one of the greatest defies currently confronting humankind which is sweeping the whole globe, with an expanding trend in developing countries. In this paper, a mathematical model (MM) was proposed to study the connection between fish consumption and CHD mortality in Egypt, by considering a system of ordinary differential equations (ODEs) involving time-fractional derivative (FD). We considered here the study on Egypt for the ease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 53 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…A new algorithm for analysing the optimal control strategies by using a SIRV disease dynamical model is mentioned in [44] . Optimal controls in the concern of preventive measures of coronary heart disease are utilized in [45] . Authors in [46] derived the optimal control model for tuberculosis infection in Atangana-Baleanu derivative sense.…”
Section: Optimal Control Problem Formulationmentioning
confidence: 99%
“…A new algorithm for analysing the optimal control strategies by using a SIRV disease dynamical model is mentioned in [44] . Optimal controls in the concern of preventive measures of coronary heart disease are utilized in [45] . Authors in [46] derived the optimal control model for tuberculosis infection in Atangana-Baleanu derivative sense.…”
Section: Optimal Control Problem Formulationmentioning
confidence: 99%
“…Reachability Analysis. It is extremely important to track desired signal with the rapidity and accuracy [42,43], which determines the therapeutic effect. However, the conventional sliding mode control usually results in low precision and convergence rate problems.…”
Section: Lemma 2 Consider the Fractional Order Equationmentioning
confidence: 99%
“…Another study in Egypt was conducted by using a mathematical model to find an association between fish consumption and mortalities due to chronic heart diseases. It was reported that when the consumption of fish from the total harvested fish increased with the avoidance of the behavioral and metabolic risk factors for coronary heart diseases, the associated mortalities decreased significantly in a specific duration of time (Ameen et al, 2020).…”
Section: Fish Oilmentioning
confidence: 99%